Financial and Efficiency Performance before and after Mergers and Acquisitions in the Indonesian Infrastructure Industry - Setiawan, Chandra; Amelia, Perina (Journal of Infrastructure Policy and Management (JIPM), 2024)
This study examines the differences in the financial and efficiency performance of several companies before and after Mergers and Acquisitions (M&A). It specifically evaluates the impacts of M&A on infrastructure industry companies listed on the Indonesia Stock Exchange by comparing their performance three years before and three years after M&A. The analysis employs non-parametric statistics, including the Wilcoxon Signed Rank Test, and Data Envelopment Analysis (DEA). The companies’ financial performance is assessed using various financial ratios: Current Ratio (CR), Debt to Equity Ratio (DER), Cash Ratio (CR), Interest Coverage Ratio (ICR), Fixed Asset Turnover (FAT), Total Asset Turnover (TATO), Return on Asset (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The data used is secondary data obtained from the Indonesia Competition Commission (ICC/KPPU), the IDX database, and the financial reports of the companies involved. The findings reveal that, overall, the financial and efficiency performance of the five companies did not improve after the M&A. Surprisingly, only one company, i.e., Adhi Karya, successfully increased its efficiency score following the M&A.